I’m Doing Better on My Own: Social Inhibition in Vocabulary Learning in Adults - Martin, Clara D.; Underwood, Amy; Molinaro, Nicola (Frontiers in Psychology, 2019)
Vocabulary learning is better achieved by children facing a teacher than when presented to the same teacher through video (so-called “video deficit” effect), which has significant implications for toddlers’ education. Since millions of adults also learn new vocabulary when acquiring a second language (L2), it is important to explore whether adults suffer from “video deficit” effects, as children do. In the present study, we report two experiments in which Spanish native late learners of English were involved in a vocabulary learning task. In Experiment 1, participants had to learn English (L2) labels associated to real objects. In Experiment 2, participants had to learn English (L2) and Spanish (L1) labels associated to novel objects. In both experiments, vocabulary learning was divided into three conditions: In the NoFace condition, participants were presented with the objects and their auditory labels, through video. In the Video condition, a teacher was showing the objects and uttering their names, through video. The Live condition was equivalent, except that the teacher was facing the participants in the room. Each condition was followed by a recall test. Better learning in Video compared to NoFace condition revealed that adults benefit from the teacher’s display with direct gaze, confirming the fundamental role of face display with direct gaze in social communication in adults. Interestingly, adults learned better through Video than in the Live condition. Those results were obtained in L2 vocabulary learning in both Experiments 1 and 2, and also generalized to native language in Experiment 2. We argue that adults suffer from social inhibition, meaning that they perform worse when in the presence of another person during task performance. In sum, we show that video-mediated teaching might not be detrimental for adults learning new vocabulary lists, as it is the case for young children. These results might have important implications for pedagogical programs targeting adults’ second language vocabulary learning, since proper acquisition of vocabulary list can be achieved through video including a teacher’s display.